Is There A Role for Governance in the Saving-Investment Nexus for Sub-Saharan Africa? (2015)
The study broke some yet to be explored ground in the literature on the Feldstein-Horioka (FH) puzzle. Precisely, it uncovered the role of institutions (particularly governance) in the saving-investment causal nexus using data on a panel of 37 sub-Saharan Africa countries, over the period spanning 1996 through 2010. Deploying a battery of panel estimators, the findings further lend support to earlier opinions on the bound of ranges of saving retention coefficients for the region. More specifically, the coefficients are -0.014, 0.200 and 0.21 in the ordinary least squares (OLS), fixed effects (FE) and random effects (RE) regressions, respectively. These estimates are largely synonymous to those reported for SSA in extant studies. Interestingly, considerable improvement was recorded in the saving coefficient from 0.20 to 0.361 when governance was interacted with saving. This concretely reinforces the useful role of governance in mobilizing saving for investment within these economies. Based on these findings, domestic resource mobilisation can be a veritable vehicle for plugging the substantial investment gap in these SSA economies. However, such policy thrust must be necessarily complemented by far-reaching governance reforms.